Unravelling the structure of peroxides with antiparasitic activity: the relative impact of a trioxolane or a tetraoxane pharmacophore on the overall molecular structure - Amado, Patrícia (2022)
Plasmodium falciparum artemisinin-resistance boosted the quest for novel plasmodial "fast killers," uncovering antimalarial candidates OZ439 and E209, whose peroxide precursors are 1,2,4-trioxolane (1) and 1,2,4,5-tetraoxane (2), differing solely in the pharmacophore (trioxolane or tetraoxane). Combining X-ray crystallography and vibrational spectroscopy, along with Hirsh-feld surface analysis and calculations (CE-B3LYP/6-31G(d,p)) of pairwise interaction energies of intermolecular contacts existing in the crystal structure, may deepen the understanding of relative reactivity and properties of these endoperoxides classes. In the crystal, the tetraoxane ring in 2 and the trioxolane-adamantyl fragment in 1 are disordered, with molecules 1 and 2 existing as two distinct, stable conformations. Whereas the dominant C-H center dot center dot center dot O H-bonds in 1 connect an adamantyl C-H and O1 or O2 of the trioxolane ring, in 2 they involve the carbonyl oxygen, acting as a double acceptor from phenyl ring C-H groups. C-H center dot center dot center dot O and C-H center dot center dot center dot pi H-bonds define the molecular packing of 2, while C-H center dot center dot center dot H-C van der Waals interactions determine the packing of 1. The dispersive component dominates the interaction energies calculated for the most representative molecular pairs.